Association between grain yield, grain quality and morpho-physiological traits along ten cycles of recurrent selection in bread wheat (triticum aestivum L.) - Maich, Ricardo Héctor (2017)
The objective of the present investigation was to examine the relationships between agronomical behavior and grain quality along ten cycles of a recurrent selection program performed under rainfed condition. Twenty-four lines, four for each one of the 0, 2, 4, 6, 8 and 10 cycles of recurrent selection, were evaluated for two consecutive years (2011 and 2012). The experimental lines were evaluated under conventional (CT) and no tillage (NT) systems. Grain yield and grain weight were determined and harvest index and grain number estimated. Flour protein content, sodium dodecyl sulphate sedimentation (IS-SDS) and lactic acid SRC (LASRC) were considered as end-use quality predictive tests. The Spearman correlation coefficient was used to measure the relationships among yield, its components and grain quality parameters. Within the context of CT, flour protein content was negatively associated with all the agronomic variables. The IS-SDS has a negative association with the grain weight; meanwhile, LASRC associated positively with all the agronomic variables. When wheat was grown in NT, the relationship between IS-SDS and harvest index, like LASRC with all agronomic traits, was positive. Confining the discussion to the CT results, after ten cycles of recurrent selection the highest grain yield achieved was accompanied by a decrease in protein percentage. However, the decrease in the percentage of protein in more advanced selection cycles was offset by an improvement of its quality.